Citation metrics as an additional indicator for evaluating research performance? An analysis of their correlations and validity - Marcel Clermont; Alexander Dirksen; Barbara Scheidt; Dirk Tunger (Business Research, 2017)
This paper investigates the potential expansion of an indicator set for research performance evaluation to include citations for the mapping of research impact. To this end, we use research performance data of German business schools and consider the linear correlations and the rank correlations between publication-based, supportive, and citation-based indicators. Furthermore, we compare the business schools in partial ratings of the relative indicators amongst themselves and with those business schools that are classified in other studies as being strong in research and/or reputable. Only low correlations are found between the citation metrics and the other indicator types. Since citations map research outcome, this is an expected result in terms of divergent validity. Amongst themselves, the citation metrics display high correlations, which, in accordance with the convergent validity, shows that they can represent research outcome. However, this does not apply to the J-factor, which is a journal-based normalizing citation metric.
Keywords: H83; I23; 650; Citation metrics; German business schools; Research performance evaluation; Research ranking; Validity